PENGARUH TINGKAT PENDAPATAN, TARIF PAJAK, DENDA PAJAK, DAN PROBABILITAS PEMERIKSAAN PAJAK TERHADAP KEPATUHAN PAJAK - Eben Ezer; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
The purpose of this paper is to examine the effect of income level, Income Tax, Fines, and Tax Audit on Tax Compliance.The sample in this study consisted of 440 of Taxpayers which is listed on one of the Directorate General of Taxation, in 2012-2014 period. Hypothesis examination are using multiple regression. The results showed that the level of income affect positively and significantly related to the level of tax compliance, tax rates do not significantly affect the level of tax compliance, tax penalties affect posititif significantly on the level of tax compliance and the probability of tax audits positive and significant effect on the level of tax compliance. Overall, the factors that are economic include income levels, tax rates, tax penalties and tax audit probabilities affect the level of taxpayer compliance